Single-shot liposomal bupivacaine in place of rectus sheath catheters to provide non-opiate analgesia after laparotomy: a quality improvement project to reduce the need for ongoing nursing input - Rob Bethune; Neil Smart; Edward Matthews; Pranu Ragatha (BMJ Open Quality, 2024)
Opioid-sparing pain management is an integral component of enhanced recovery after colonic and rectal surgery. In our hospital, rectus sheath catheters (RSCs) are routinely placed during emergency laparotomy for colorectal procedures to allow a postoperative compartmental block of the surgical site with repeated doses of bupivacaine. However, RSCs require a significant amount of clinical nursing time to maintain and ‘top-up’. We present a quality improvement project in which we administered single-shot liposomal bupivacaine (LB) intraoperatively as an alternative to bolus doses of conventional bupivacaine delivered through RSCs. Having thereby reduced the demands placed on nursing time through a reduction in the use of RSCs, we sought to establish whether there was any associated change in analgesic efficacy. Patient pain scores, use of patient-controlled analgesia (PCA) and length of stay following surgery were analysed before and after the introduction of LB. No disruption in these outcomes was identified using statistical process control analysis. A direct comparison of results for patients who received LB versus those who received bolus dosing of bupivacaine via RSCs found no significant differences, with a median total PCA dose of 270 mg oral morphine equivalents (OME) for patients who received LB versus 396 mg OME for patients who had RSCs (p=0.54). The median length of stay for patients who received LB was 15.5 days versus 16 days for those who had RSCs (p=0.87). We conclude that LB represents a viable alternative to boluses of conventional bupivacaine via RSCs in promoting enhanced recovery after emergency laparotomy and look to extend its use locally.